Gambaran Dukungan Sosial Keluarga Pada Pasien Tb Paru Rumah Sakit Harapan Pematangsiantar - Imelda Derang; Murni Sari Dewi.Simanullang; Erlina Malau (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis as an acid-resistant bacteria (BTA), which attacks the respiratory organs of the lungs and even to all parts of the body, this is what makes TB patients feel helpless, therefore it is necessary to have family support intact bio, psycho, social and spiritual are important factors for the success of TB treatment and accelerate the healing process. This study aims to identify features of family social support for pulmonary TB sufferers at Harapan Siantar Hospital in 2023. The research method used is descriptive. The research population is 65 respondents, with a total sampling technique. The instrument used is a questionnaire. The results showed that 47 people (72.3%) had good family social support, and 18 people (27.7%) had enough. It is hoped that families and health services will continue to accompany family members who have TB to speed up the healing process.